2012
DOI: 10.1002/ar.22435
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Sexual Segment of the Kidney of Snakes with Emphasis on Ultrastructure in the Yellow‐Bellied Sea Snake, Pelamis platurus

Abstract: The sexual segment of the kidney (SSK) is an accessory sex structure in male lizards and snakes (Squamata). We describe histology of the SSK in 12 species of snakes, including one from the basal Scolecophidia, Leptotyphlops dulcis, and from the more advanced Alethinophidia, species from the Acrochordidae (Acrochordus granulatus), Homalopsidae (Cerberus rynchops), Uropeltidae (Teretrurus sanguineus), and eight species from the Elapidae, including six species of sea snakes. We also describe the ultrastructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The hypertrophy of the SSK and the production of secretory granules culminates during the breeding phase. The highly columnar cells of the SSK are loaded with secretory granules and the euchromatic nuclei are pushed towards the basal membranes as in other squamates (Gabri, 1983; Kuhnel & Krisch, 1974; Rheubert et al, 2011; Sever et al, 2008; Sever & Hopkins, 2005; Siegel et al, 2009), unlike centrally placed nuclei in a couple of snakes (Sever et al, 2002, 2012). A marked reduction of the cells of the SSK from columnar to cuboidal, accompanied by reduction in the secretory granules, was observed during the post‐breeding phase.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The hypertrophy of the SSK and the production of secretory granules culminates during the breeding phase. The highly columnar cells of the SSK are loaded with secretory granules and the euchromatic nuclei are pushed towards the basal membranes as in other squamates (Gabri, 1983; Kuhnel & Krisch, 1974; Rheubert et al, 2011; Sever et al, 2008; Sever & Hopkins, 2005; Siegel et al, 2009), unlike centrally placed nuclei in a couple of snakes (Sever et al, 2002, 2012). A marked reduction of the cells of the SSK from columnar to cuboidal, accompanied by reduction in the secretory granules, was observed during the post‐breeding phase.…”
Section: Discussionmentioning
confidence: 98%
“…Histochemical studies on 73 species of squamates representing 19 families found that the SSK was rich in protein secretion, but the PAS/AB reaction was quite variable (Saint Girons, 1972). Studies on snakes have shown that the secretory granules show PAS + reaction indicating the presence of neutral carbohydrates and Brilliant Indocyanine (BB) + reaction for proteins (Rojas et al, 2013; Sever et al, 2002, 2008, 2012; Siegel et al, 2009), except for the snake Teretrurus sanguineus which showed PAS—reaction (Sever et al, 2012). The secretory granules among most of the lizards have also shown positive reaction for PAS + and MBB + (Del Conte, 1972; Rheubert et al, 2011, 2015; Sever & Hopkins, 2005) except for the two neotropical lizards; N. frenata and A. dorsivittatum whose secretory granules have shown negative reaction for PAS—(Novelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations